Politicizing sex in contemporary Africa: homophobia in Malawi - Currier, Ashley (Cambridge University Press, 2019)
Although sexual minorities in Africa continue to face harsh penalties for same-sex relationships, strong anti-homophobic resistance exists across the continent. This book systematically charts the emergence and effects of politicized homophobia in Malawi and shows how it has been used as a strategy by political elites to consolidate their moral and political authority, through punishing LGBT people and dividing social movements. Here, Ashley Currier pays particular attention to the impact of politicized homophobia on different social movements, specifically HIV/AIDS, human rights, LGBT rights, and women's rights movements. Her timely account intervenes in Afro-pessimist portrayals of the African continent as a hotbed of homophobia and unravels the tensions and contradictions underlying Western perceptions of Malawi. It shows that, in reality, many lesbian, gay, bisexual, and transgender people happily call Malawi home, in spite of heightened antigay vitriol that has generated unwanted visibility for them.